Strategi Promosi Untuk Meningkatkan Minat Baca di Perpustakaan SMAIT Al-Ittihad Pekanbaru - Meisya, Aya; Hasanah, Lailatul; Ramadhani, Rezka Devi (CV. ITTC INDONESIA, 2022)
This research was conducted to find out the promotional strategies carried out by researchers at SMAIT AL-ITTIHAD Pekanbaru for students through promotions carried out by the SMAIT AL-ITTIHAD Pekanbaru library. In this study, using a descriptive method with a form of qualitative research. Qualitative research methods that focus on observing events, phenomena, which are studied in complex, unrecognizable social characters. Data collection techniques using observation, documentation and interviews. From the results of this study it appears that the promotion strategy can increase students' reading interest in the SMAIT AL-ITTIHAD Pekanbaru library. There are several ways that are used to promote the library, including: outreach, journalistic seminars held in the library, through competitions held in the library, and the flagship program is the mini library in every class, and there are also bulletin boards where books are placed as promotion media